Efficacy of iGlarLixi, a fixed‐ratio combination of insulin glargine and lixisenatide, in patients with type 2 diabetes stratified as at high or low risk according to HEDIS measurements. Issue 11 (24th July 2018) - Sugimoto, Danny H.; Dex, Terry; Stager, William; Aroda, Vanita R.
Abstract : The Healthcare Effectiveness Data and Information Set (HEDIS) measurements assess glycaemic goal attainment in patients with type 2 diabetes, incorporating factors including age and health status. Healthier patients are assigned a glycated haemoglobin (HbA1c) goal of <7% (low‐risk [LR]) and individuals aged >65 years or with comorbidities are assigned a goal of <8% (high‐risk [HR]). This post‐hoc analysis assessed the safety and efficacy of iGlarLixi, a fixed‐ratio combination of insulin glargine 100 U/mL (iGlar) and lixisenatide, in 1898 patients from the phase 3 LixiLan‐L and LixiLan‐O clinical trials, retrospectively classified as LR ( n = 1181) or HR ( n = 717). iGlarLixi was more effective in reducing HbA1c than comparators in both LR and HR patients across the LixiLan‐L trial (change from baseline, 1.1% vs −0.6% for iGlar in both groups; P < 0.001) and the LixiLan‐O trial (change from baseline, LR/HR −1.6%/−1.4% vs −1.3%/−1.2% for iGlar and −0.8%/−0.9% for lixisenatide; P < 0.01). iGlarLixi treatment significantly reduced postprandial glucose in both LR and HR patients ( P < 0.001). The incidence of hypoglycaemia did not differ between risk categories in any treatment group.